Subspace-constrained SINR optimization in MIMO full-duplex relays under limited dynamic range - Emilio Antonio-Rodríguez; R. López-Valcarce; Taneli Riihonen; Stefan Werner; Risto Wichman (IEEE 16th Int. Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2015)
We propose a method for maximizing the signal-to-interference-plus-noise ratio (SINR) in a wideband full-duplex MIMO regenerative relay that accounts limited dynamic range of the receiver and transmitter impairments. Transmit and receive filters are designed at the relay, by means of an alternating minimization algorithm, to minimize the interference at the decoder input in the destination node. We impose channel shortening and subspace constraints to ensure that the received signal at the destination is not compromised. Simulation results show that the presented method significantly outperforms other constrained approaches.
Keywords: adaptive signal processing; compass; full duplex